2022
DOI: 10.3389/fcell.2022.842153
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus Suppresses Tumorigenesis of Oropharyngeal Cancer via Enhancing Anti-Tumor Immune Response

Abstract: Deficiency in T cell-mediated adaptive immunity, such as low CD8+ T cell infiltration, inhibits the immune surveillance, promotes malignant transformation, and facilitates tumor growth. Microbiota dysbiosis diminishes the immune system and contributes to the occurrence of cancer. However, the impact of oral dysbiosis on the occurrence and molecular mechanisms of oropharyngeal cancer (OPC) remains largely unknown. In the current study, we used 4-nitroquinoline-1-oxide (4NQO) to mimic tobacco-related carcinogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…This observation raises the question whether the oral microbiome influenced the higher T cell frequency at this site, since it is reported that microbes residing in the oral cavity could affect the TIME by enhancing the influx of T cells. 32 However, when comparing the immune composition of tumor-adjacent mucosal tissue originating from oral cavity to mucosa from the larynx and hypopharynx, a difference was not detected. This suggests that the oral microbiome, at least in normal tissue, did not affect the abundance of T cells at this anatomical site.…”
Section: Discussionmentioning
confidence: 95%
“…This observation raises the question whether the oral microbiome influenced the higher T cell frequency at this site, since it is reported that microbes residing in the oral cavity could affect the TIME by enhancing the influx of T cells. 32 However, when comparing the immune composition of tumor-adjacent mucosal tissue originating from oral cavity to mucosa from the larynx and hypopharynx, a difference was not detected. This suggests that the oral microbiome, at least in normal tissue, did not affect the abundance of T cells at this anatomical site.…”
Section: Discussionmentioning
confidence: 95%
“…Endogenous peroxidase blocking, antibody action, and development were performed as reported 51 . Quantification of positive areas in intestinal epithelial cells was completed using IHC plugin of ImageJ software 52 , 53 .…”
Section: Methodsmentioning
confidence: 99%
“…The slides were then incubated with biotinylated secondary antibodies and developed using peroxidase streptavidin and 3,3'-diaminobiphenylamine tetrahydrochloride (DAB) for 1 min. The nuclei were finally stained with hematoxylin [36] .…”
Section: Immunohistochemistrymentioning
confidence: 99%